Health-industry linkages for local health: reframing policies for African health system strengthening. Issue 4 (19th March 2018) - Mackintosh, Maureen; Mugwagwa, Julius; Banda, Geoffrey; Tibandebage, Paula; Tunguhole, Jires; Wangwe, Samuel; Karimi Njeru, Mercy
Abstract: The benefits of local production of pharmaceuticals in Africa for local access to medicines and to effective treatment remain contested. There is scepticism among health systems experts internationally that production of pharmaceuticals in sub-Saharan Africa (SSA) can provide competitive prices, quality and reliability of supply. Meanwhile low-income African populations continue to suffer poor access to a broad range of medicines, despite major international funding efforts. A current wave of pharmaceutical industry investment in SSA is associated with active African government promotion of pharmaceuticals as a key sector in industrialization strategies. We present evidence from interviews in 2013–15 and 2017 in East Africa that health system actors perceive these investments in local production as an opportunity to improve access to medicines and supplies. We then identify key policies that can ensure that local health systems benefit from the investments. We argue for a 'local health' policy perspective, framed by concepts of proximity and positionality, which works with local priorities and distinct policy time scales and identifies scope for incentive alignment to generate mutually beneficial health–industry linkages and strengthening of both sectors. We argue that this local health perspective represents a distinctive shift in policy framing: it is not necessarily in conflict with 'global health' frameworks but poses a challenge to some of its underlying assumptions.